A study on the photoisomerization of phenylpropanoids and the differences in their radical scavenging activity using in-situ NMR spectroscopy and on-line radical scavenging activity analysis - Sangah Park; Hojin Kim; Miyeon Bang; Byung-Hun Um; Jin Wook Cha (Applied Biological Chemistry, 2024)
Abstract Phenylpropanoids are naturally occurring secondary metabolites that exhibit various biological activities such as ultra-violet (UV) light protection and reactive-oxygen species (ROS) scavenging. In this study, we utilized a light-emitting diode (LED) based in-situ UV irradiation nuclear magnetic resonance (NMR) technique to monitor the photoisomerization reactions of these phenylpropanoids under UV irradiation in real-time. Through this approach, we measured the photochemical reaction rates and photostationary state (PSS) ratios of these molecules and observed distinct reaction rate and PSS ratio information depending on the variation of substituent groups in each phenylpropanoid molecule. We also evaluated the radical scavenging activity (RSA) for each photochemical product through diphenyl-1-picrylhydrazyl radical (DPPH) assay and 2,2’-azino-bis(3-ethylbenzenthiazoline-6-sulphonic acid) (ABTS) assay. We found that the photoisomerization product of caffeic acid can increase both DPPH and ABTS radical scavenging activities, and confirmed the enhanced ABTS radical scavenging ability of caffeic acid cis-isomer based on the online high-pressure liquid chromatography (HPLC)-ABTS analysis and the PSS ratio information of each isomer.